2018
DOI: 10.1039/c8bm00300a
|View full text |Cite
|
Sign up to set email alerts
|

Peptide coatings enhance keratinocyte attachment towards improving the peri-implant mucosal seal

Abstract: There is a critical need for preventing peri-implantitis as its prevalence has increased and dental implants lack features to prevent it. Research strategies to prevent peri-implantitis have focused on modifying dental implants to incorporate different antimicrobial agents. An alternative strategy consists of barring the expansion of the biofilm subgingivally by forming a long-lasting permucosal seal between the soft tissue and the implant surface. Here, we innovatively biofunctionalized titanium with bioinspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…Previously, scholars have focused on improving epithelial biological sealing around implants and HD formation by coating titanium surfaces with LM332 or LM332-derived peptides. 14 , 15 , 16 , 17 , 18 However, exogenous LM332, as a macromolecular protein, can cause immune rejection in the body and rapid protein degradation. Furthermore, protein synthesis can be expensive and suboptimal for clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, scholars have focused on improving epithelial biological sealing around implants and HD formation by coating titanium surfaces with LM332 or LM332-derived peptides. 14 , 15 , 16 , 17 , 18 However, exogenous LM332, as a macromolecular protein, can cause immune rejection in the body and rapid protein degradation. Furthermore, protein synthesis can be expensive and suboptimal for clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, many studies have demonstrated that laminin332 is an important component in IBL and interacts with integrin α6β4 to form HDs (Yamashita et al, 2010;Koidou et al, 2018). As Langhofer's study reported, keratinocytes cultured on the extracellular matrix secreted by 804G cells (mainly containing laminin332) were induced to "trigger" hemidesmosome assembly (Langhofer et al, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Given this popularity, a number of different peptide immobilization chemistries have been used to anchor peptides to a material surface [ 3 , 4 ]. Such peptide immobilization chemistries have been exploited to create a number of exciting peptide-based strategies for surface engineering of biomedical surfaces (among others): cell adhesion surfaces [ 5 , 6 ] using so called “cell adhesion peptides” [ 7 , 8 ], antimicrobial surfaces [ 9 , 10 ], combined antimicrobial and cell adhesion surfaces [ 11 13 ], biosensors [ 14 ], selective attachment of cells [ 15 , 16 ], tri-biomolecule surfaces [ 17 ], antifouling surfaces [ 18 ], and biomineralization [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other biomedical devices suffer a similar fate [ 32 ]; implantable auditory assist devices demonstrate a 26% failure rate [ 33 ] and infections occur in up to 77% of individuals with bone-anchored orthopaedic devices [ 34 ]. We have selected the peptide LamLG3 identified [ 35 ] from a globular module (LG3) of laminin332 (LM332) capable of inducing hemidesmosome (HD) formation from oral keratinocytes in the soft tissue surrounding dental implants [ 5 , 36 , 37 ]. HDs are a transmembrane “link” or “rivet” between teeth and gingiva ( Figure 1 ), as the gingiva forms a protective, physical barrier for the tooth, or dental implant, against biofilm invasion [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%